2021
DOI: 10.3389/fmicb.2020.603927
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequencing Analysis of Scleromitrula shiraiana, a Causal Agent of Mulberry Sclerotial Disease With Narrow Host Range

Abstract: Scleromitrula shiraiana is a necrotrophic fungus with a narrow host range, and is one of the main causal pathogens of mulberry sclerotial disease. However, its molecular mechanisms and pathogenesis are unclear. Here, we report a 39.0 Mb high-quality genome sequence for S. shiraiana strain SX-001. The S. shiraiana genome contains 11,327 protein-coding genes. The number of genes and genome size of S. shiraiana are similar to most other Ascomycetes. The cross-similarities and differences of S. shiraiana with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…In the genome of E. weberi, a specific parasite of ant cultivated Leucoagaricus spp., the depletion of CAZymes was also found [100]. There were fewer genes encoding cell wall-degrading enzymes and effector proteins in the genome of Sclerotinia shiraiana than those of Sclerotinia sclerotiorum and B. cinerea, which was probably a key factor of the narrow host range of S. shiraiana [88].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the genome of E. weberi, a specific parasite of ant cultivated Leucoagaricus spp., the depletion of CAZymes was also found [100]. There were fewer genes encoding cell wall-degrading enzymes and effector proteins in the genome of Sclerotinia shiraiana than those of Sclerotinia sclerotiorum and B. cinerea, which was probably a key factor of the narrow host range of S. shiraiana [88].…”
Section: Discussionmentioning
confidence: 83%
“…For the congeneric fungi, Calcarisporium parasiticum has been observed to parasitize several species of Physalospora and closely related fungi [87]. Scleromitrula shiraiana is a causal agent of mulberry sclerotial disease with a narrow host range but includes some species of genus Morus [88].…”
Section: Discussionmentioning
confidence: 99%
“…shiraiana had fewer cell wall‐degrading enzymes and effector proteins, and C . shiraiana had fewer effector proteins, which may be related to their narrow host range (Lv, He, et al, 2021; Zhu et al, 2021). The differences in the genome composition of the pathogens of mulberry sclerotial disease indicate that they have different infection mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome sequencing of mulberry fruits infected with C. shiraiana and C. carunculoides showed that pathogen infection stimulated the host's secondary metabolic pathways and defence-related hormone pathways (Bao et al, 2020;Lv, Hao, et al, 2021). The activation of salicylic acid signalling regulated by pathogens may be beneficial to infection by the pathogens (Lv, Hao, et al, 2021). However, it is not clear what effect the replacement of the dominant pathogen or the change of composition ratio of pathogens can have on disease occurrence.…”
mentioning
confidence: 99%
See 1 more Smart Citation